A Crystal Growth Method for Water - Qian, Jin; Fan, Jing; Deng, Ni; Shi, Hong; Shu, Kangying (Asian Journal of Chemistry, 2012)
Water is crystallized into ice using a simple setup and F12 mm × 16 mm ice have been achieved. It proves the feasibility of a method to grow crystal. This method is very similar with the temperature gradient technique. But the crystal growth direction is verse with the temperature gradient technique. This method can grow crystal from the top to the bottom of the crucible. The key point of this method is the special crucible shape. Some of the potential advantages and disadvantages of this method are discussed.